Developing the KATAKU Mobile Application to Enhance Vocabulary Acquisition for Deaf Students - Farid, Achmad; Syafrudin, Tomy; Farhan, Ahmad; Qonita, Niswa; Prastyo, Arya Teguh (Yayasan Pendidikan Bima Berilmu, 2024)
This study presents the development of the KATAKU (Kata untuk Tunarungu Interaktif dan Unik) application as an educational tool designed to support vocabulary learning for deaf students. Deaf students, who have the same educational rights as their hearing peers, often attend Special Schools (SLB). The integration of visual aids and technology in learning has proven effective in increasing their engagement and interest. This study employed a mixed-methods approach, including vocabulary assessments for deaf students, classroom observations, and teacher interviews for a needs analysis to identify the specific requirements of schools and students. Results from the vocabulary assessments revealed that deaf students face significant challenges, particularly with academic terms and word categorization. Classroom observations at three SLB schools in Jombang highlighted engaging but challenging learning dynamics, reinforcing the need for accessible and efficient teaching tools for educators. Teacher interviews indicated that using the paper dictionary provided by the Ministry of Education can be time-consuming and lacks efficiency. This study concludes that deaf students in Jombang face substantial obstacles in vocabulary comprehension, especially with academic vocabulary. The findings underscore the need for targeted vocabulary interventions using modern technological tools to better prepare students for advanced educational demands.